Prevalence, severity, and self-management of depressive mood among community-dwelling people with spinal cord injury in Nepal - Mandira Baniya; Luppana Kitrungrote; Jintana Damkliang (Belitung Nursing Journal, 2022)
Background: Depression is a common psychological condition after spinal cord injury. There are increased incidences of self-harm, suicidal behavior, and lower quality of life among people with spinal cord injury and depression. However, self-management of depressive symptoms in the community is less explored. Objective: This study aimed to examine the prevalence, severity, and self-management of depressive mood in community-dwelling people with spinal cord injury. Methods: A descriptive study was conducted in 2019 among 115 people with spinal cord injury discharged from three health centers and living in the 13 districts of Bagmati Province. Participants were selected using stratified random sampling. Questionnaires were related to demographics, health and environment, depressive mood, and self-management. Descriptive statistics and quantitative content analysis were used to analyze the data. Results: Ninety-seven (84.3%) people with spinal cord injury had a depressive mood. Of these, 60.8% had moderate to severe depressive moods. They mainly used the internet and social media, shared feelings with family members, and practiced Hindu religious activities for depressive mood management because of the physical barriers to accessing a healthcare facility and easiness to use of non-pharmacological methods. Nearly half of participants who used sharing of feelings felt their depressive mood disappeared when they often used the method. Conclusion: Depressive mood following initial hospitalization is highly prevalent among people with spinal cord injury in Nepal, most of whom live in rural settings. Therefore, nurses and other health professionals should provide psychoeducation for this population and their family members to better address mental health problems. Facilitating pathways for those in rural areas to engage in social activities and timely treatment access may improve depressive mood. Nurses and other rehabilitation professionals can use social media to assess depressive moods and deliver management approaches in the community.